-t+9=t+14

Simple and best practice solution for -t+9=t+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -t+9=t+14 equation:



-t+9=t+14
We move all terms to the left:
-t+9-(t+14)=0
We add all the numbers together, and all the variables
-1t-(t+14)+9=0
We get rid of parentheses
-1t-t-14+9=0
We add all the numbers together, and all the variables
-2t-5=0
We move all terms containing t to the left, all other terms to the right
-2t=5
t=5/-2
t=-2+1/2

See similar equations:

| x^2+(x+6)^2=90 | | k/7.1+98.5=18.8 | | x-1=3×+3 | | 2x-5=3/5 | | 2(x-11)=-38 | | 1/x+2+2=11/x+2 | | X.10x=30 | | 18x=4.51 | | x*x+(x*x+6*6)=90 | | v+163= 9 | | 5x=3-7(3x-2) | | -90x^2+8100x=x | | 5+p=-18 | | x*x+(x*x+6)=90 | | 7x-x=30= | | v+16/3=9 | | (6c-5)+(-6c)=0 | | 5(v+2)=40 | | 65+15x=-35 | | 9.8x+34.93=-10.2x+34.71 | | 13=m/3+10 | | 2y+y=5y+7 | | 600=9m+60 | | 12x^2+5x-42=0 | | x18=4.5 | | 17-+2c=24 | | 6x+20+x+40+4x-5=180 | | 10.5=(2+5)×h÷2 | | x15=2030 | | 2a-3a=-4= | | 19-g=7;g=15 | | 3x^2+60=180 |

Equations solver categories